Scabies epidemiology in health care centers for refugees and asylum seekers in Greece. - Christina Louka; Emmanouil Logothetis; Daniel Engelman; Eirini Samiotaki-Logotheti; Spyros Pournaras; Ymkje Stienstra (Public Library of Science (PLoS), 2022)
Background Scabies is a global health concern disproportionately affecting vulnerable populations such as refugees and asylum seekers. Greece is a main point of entry in Europe for refugees, but epidemiological data on scabies in this population are scarce. We aimed to describe the epidemiology of scabies, including trends over the study period. Methodology/principal findings Data were collected from June, 2016 to July, 2020, using the surveillance system of the Greek National Public Health Organization. Daily reports on scabies and other infectious diseases were submitted by staff at health centers for refugees/asylum seekers. Observed proportional morbidity for scabies was calculated using consultations for scabies as a proportion of total consultations. There were a total of 13118 scabies cases over the study period. Scabies was the third most frequently observed infectious disease in refugees/asylum seekers population after respiratory infections and gastroenteritis without blood in the stool. The scabies monthly observed proportional morbidity varied between 0.3% (August 2017) to 5.7% (January 2020). Several outbreaks were documented during the study period. The number of cases increased from October 2019 until the end of the study period, with a peak of 1663 cases in January 2020, related to an outbreak at one center. Spearman correlation test between the number of reported scabies cases and time confirmed an increasing trend (ρ = 0.67). Conclusions/significance Scabies is one of the most frequently reported infectious diseases by health care workers in refugee/asylum seekers centers in Greece. Observed proportional morbidity for scabies increased over time and there were several outbreaks. The current surveillance system with daily reports of the new cases effectively detects new cases in an early stage. Public health interventions, including mass drug administration, should be considered to reduce the burden of scabies in refugee/migrant populations.